The Deep End: A Memoir of Growing Up - Callaghan, Mary Rose (University Press Copublishing Division, 2016)
One day, when Mary Rose Callaghan was 13, her mother jumped into the freezing Irish Sea. Knowing that her mother was an asthmatic, the shock of seeing her dive into “the deep end” began Mary Rose’s curiosity about her mother’s life. That curiosity spawned the writing of this memoir, a coming-of-age tale focused on Mary Rose’s relationship with her mother, which endured through economic hardship, and her mother’s descent into mental illness and alcoholism. The Deep End begins by tracing her mother’s arrival in Ireland in the 1930s, training to be a nurse, and marriage to Mary Rose’s father, continues through Mary Rose’s difficult childhood and later success as a writer, and culminates with her marriage to Robert Hogan and her mother’s death.